ANALISIS EMPIRIS HUBUNGAN LEMBAGA KEUANGAN SYARIAH DAN KEMISKINAN DI INDONESIA: STUDI PADA PERBANKAN SYARIAH, SAHAM SYARIAH, DAN ASURANSI SYARIAH - Al Badri, Ziddan Muhammad (Universitas Dharmawangsa, 2025)
This study examines the impact of Islamic financial institutions on poverty in Indonesia, focusing on the roles of Islamic banks, Islamic shares, and Islamic insurance. Utilizing secondary time-series data from 2014 to 2023 obtained from the Financial Services Authority, this research employs the Ordinary Least Squares (OLS) method with multiple linear regression analysis. The findings reveal that Islamic banks do not have a significant effect on poverty reduction, suggesting potential limitations in financial accessibility for low-income groups. In contrast, Islamic shares and Islamic insurance demonstrate a significant negative effect on poverty, indicating that capital market investment and financial protection mechanisms contribute to poverty alleviation. These results provide insights into the differential roles of Islamic financial sectors in economic development and highlight the need for inclusive financial policies to enhance the impact of Islamic banking on poverty reduction.